THE EFFECT OF THIRD PARTY FUNDS ON FINANCING IN PT. VICTORIA SHARIA BANK - marahombang rambe; abdul nasser hasibuan; muhammad wandisyah; idris saleh (Institut Agama Islam Negeri Padangsidimpuan, 2020)
This research is motivated by financing which is one of the main activities of the Islamic bank Victoria running its business, which based on the published financial statements of PT.Bank Victoria published financial statements of PT.Bank Victoria Syariah financing development is not in line with the development of third party fuds. The phenomenon that occurs in this study is seen from the decline and increase in third-party funds is not in accordance with the decrease and increase in financing. The purpose of this study was to determine the effect of third party funds on financing at PT Bank Victoria Syariah in 2016- 2018. This type of research is quantitative research, with the source of data used is secondary data in the form of time series from 2016-2018 as many as 36 samples. Data was obtained through the Bank Victoria Syariah and Ojk website. Data analysis, normality test, simple regression analysis, detremination test (R2), hypothesis test ( test t), with data processedusing SPSS Version 23 statistical calculations. The results of the study with the coefficient determination test the percentage contribution of the influence of variable third party funds to financing is 58.8%. While the remaining 41.2% is in this study. Partially (t test) shows that third party funds significantly influence the financing of PT Bank Victoria Syariah in 2016- 2018.